2021
DOI: 10.1021/acsanm.0c03032
|View full text |Cite
|
Sign up to set email alerts
|

Scalable Drop-to-Film Condensation on a Nanostructured Hierarchical Surface for Enhanced Humidity Harvesting

Abstract: Active cooling-based atmospheric water generators, despite their growing demand, continue to be energy intensive and offer poor collection efficiencies (energy consumption per liter of water production). Despite progress in micro-/ nanofabrication techniques and functional coatings, advanced surfaces have not been successfully scaled onto such harvesters to accelerate condensation and improve their efficiencies. Here, we present a scalable dualnanostructured hierarchical surface that comprises sporadically dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(8 citation statements)
references
References 28 publications
0
8
0
Order By: Relevance
“…Assuming spherical droplet shapes for SS-PA-P, SS-PY-PA-P, and SS-CA-PA-P, the calculated condensate water masses for each droplet are 0.38 mg, 2.14 mg, and 1.15 mg, respectively. Higher water mass indicates higher water harvest rate and higher latent heat transfer coefficient (HTC) in accordance to equation 8 [3].…”
Section: Water Condensationmentioning
confidence: 71%
“…Assuming spherical droplet shapes for SS-PA-P, SS-PY-PA-P, and SS-CA-PA-P, the calculated condensate water masses for each droplet are 0.38 mg, 2.14 mg, and 1.15 mg, respectively. Higher water mass indicates higher water harvest rate and higher latent heat transfer coefficient (HTC) in accordance to equation 8 [3].…”
Section: Water Condensationmentioning
confidence: 71%
“…This may have caused, for the range of degree of subcooling and humidity ratio difference investigated here, the peak of the rough structures on the SHL copper and aluminum substrates to remain dry and protruded above the thin film. 32 , 35 , 52 These regions act as the sites for a high rate of heterogeneous nucleation despite having the substrate exhibiting an overall thin-filmwise condensation. As a result, at steady state, the rate of condensate formation in the thin-film regime is higher than that in the rivulet regime.…”
Section: Results and Discussionmentioning
confidence: 99%
“…Table summarizes the research articles that reported the overall condensation rate on the nonwetting superhydrophobic and wetting superhydrophilic surfaces in the atmospheric humid air conditions. Clearly, the majority of the works cited in Table report that filmwise mode is more effective than dropwise mode for humidity harvesting. However, these observations did not receive comprehensive attention and, as a consequence, have remained a mystery. This result is contradictory to the general perception about the heat transfer efficiency of dropwise and filmwise modes of condensation under pure vapor conditions, but a plausible reason has not yet been addressed.…”
Section: Introductionmentioning
confidence: 99%
“…Copyright 2013, American Chemical Society, Washington, DC. Panel (b)­(i) was reproduced with permission from ref . Copyright 2021, American Chemical Society, Washington, DC.…”
Section: Applicationsmentioning
confidence: 99%